Aligning Climate Change Mitigation and Agricultural Policies in Eastern Europe and Central Asia - Larson, Donald F. (The World Bank, 2012)
Greenhouse gas emissions are largely determined by how energy is created and used, and policies designed to encourage mitigation efforts reflect this reality. However, an unintended consequence of an energy-focused strategy is that the set of policy instruments needed to tap mitigation opportunities in agriculture is incomplete. In particular, market-linked incentives to achieve mitigation targets are disconnected from efforts to better manage carbon sequestered in agricultural land. This is especially important for many countries in Eastern Europe and Central Asia where once-productive land has been degraded through poor agricultural practices. Often good agricultural policies and prudent natural resource management can compensate for missing links to mitigation incentives, but only partially. At the same time, two international project-based programs, Joint Implementation and the Clean Development Mechanism, have been used to finance other types of agricultural mitigation efforts worldwide. Even so, a review of projects suggests that few countries in Eastern Europe and Central Asia take full advantage of these financing paths. This paper discusses mitigation opportunities in the region, the reach of current mitigation incentives, and missed mitigation opportunities in agriculture. The paper concludes with a discussion of alternative policies designed to jointly promote mitigation and co-benefits for agriculture and the environment